PENGARUH BRAND IMAGE DAN KARAKTERISTIK PRODUK LANEIGE TERHADAP KEPUTUSAN PEMBELIAN - Chelsea Alicia; Valentine Siagian (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
This research aims to find out if brand image and product characteristics influence purchasing decisions. Data collection was conducted using questionnaires of research instruments. The population in this study was students from Parahyangan University. The sample number was 206 respondents who were studying at Parahyangan University Bandung with purposive sampling method. T-test results show that brand images have a positive and significant effect on purchasing decisions and product characteristics have a positive and significant impact on purchasing decisions. F-test results show there is a simultaneous influence of brand image and product characteristics on purchasing decisions. The implications of this research are expected to be used as an advanced research material and can add references to the variables studied. Companies are expected to maintain and increase the excellence of their products so that they will increase purchases in order to grow with the times.